Diego Mexía de Fernangil: religious poetry and social criticism in 17th-century Peru - Salvatierra, María de Fátima (2022)
This paper discusses La segunda parte del Parnaso Antártico de divinos poemas (1617) (Antarctic Parnassus, Part Two: Poems of the Divine), by Diego Mexía de Fernangil, whose manuscript is in the National Library of France, with the purpose of extracting some appraising samples of a literary text of the 17th century that leads to a critique of Peruvian society, after the first eighty years of the settlement of European institutions. The work under analysis has been selected because it belongs to an author highly representative of the national literature of the 1600s and because it is a famous literary text, although hardly published. Diego Mexía was a book inquisitor, conspicuous member of the Academia Antártica (Antarctic Academy), traveler and notable cultural disseminator. In several passages of his poetry, he cries out about the moral deterioration of the Peruvian social system, dating back four hundred years. We believe that studies such as this one evidence that the current cases of corruption in Peru are not surprising episodes, but have remote manifestations.